The contribution of functional antimalarial immunity to measures of parasite clearance in therapeutic efficacy studies of artemisinin derivatives - O'Flaherty, K; Ataíde, R; Zaloumis, S; Ashley, E; Powell, R; Feng, G; Reiling, L; Dondorp, A; Day, N; Dhorda, M; Fairhurst, R; Lim, P; et al. (Oxford University Press, 2019)
Background Antibodies to the blood stages of malaria parasites enhance parasite clearance and antimalarial efficacy. The antibody subclass and functions that contribute to parasite clearance during antimalarial treatment and their relationship to malaria transmission intensity have not been characterized. Methods Levels of immunoglobulin G (IgG) subclasses and C1q fixation in response to Plasmodium falciparum merozoite antigens (erythrocyte-binding antigen [EBA] 175RIII-V, merozoite surface protein 2 [MSP-2], and MSP-142) and opsonic phagocytosis of merozoites were measured in a multinational trial assessing the efficacy of artesunate therapy across 11 Southeast Asian sites. Regression analyses assessed the effects of antibody seropositivity on the parasite clearance half-life (PC½), having a PC½ of ≥5 hours, and having parasitemia 3 days after treatment. Results IgG3, followed by IgG1, was the predominant IgG subclass detected (seroprevalence range, 5%–35% for IgG1 and 27%–41% for IgG3), varied across study sites, and was lowest in study sites with the lowest transmission intensity and slowest mean PC½. IgG3, C1q fixation, and opsonic-phagocytosis seropositivity were associated with a faster PC½ (range of the mean reduction in PC½, 0.47–1.16 hours; P range, .001–.03) and a reduced odds of having a PC½ of ≥5 hours and having parasitemia 3 days after treatment. Conclusions The prevalence of IgG3, complement-fixing antibodies, and merozoite phagocytosis vary according to transmission intensity, are associated with faster parasite clearance, and may be sensitive surrogates of an augmented clearance capacity of infected erythrocytes. Determining the functional immune mechanisms associated with parasite clearance will improve characterization of artemisinin resistance.